Equality, diversity, inclusion: ensuring a resilient future for geomorphology. Issue 1 (22nd November 2020) - Tooth, Stephen; Viles, Heather A.
ABSTRACT: Within and beyond academia, debates around equality, diversity and inclusion (EDI) have been gathering pace. We focus on EDI and geomorphology and address four main questions: (1) why does EDI matter for geomorphology?; (2) what are the barriers to greater EDI in geomorphology?; (3) how can we address these EDI barriers?; (4) can we ensure a resilient future for geomorphology by addressing EDI? At a time of critical environmental, social and economic transition, we contend that addressing EDI is essential for ensuring a resilient geomorphology, defined here as a discipline that is seen to be adapting to these changing external circumstances so that it remains relevant, vibrant and accessible to a wide cross‐section of society. Not doing so will limit the intellectual development of geomorphology, incur reputational risk for geomorphological groups and organizations like the British Society for Geomorphology, and ensure that the many potential benefits of geomorphology for science and society remain underutilized at best. © 2020 John Wiley & Sons, Ltd.